Lending pro-cyclicality and macroprudential policy: Evidence from Japanese LTV ratios - Ono, Arito; Uchida, Hirofumi; Udell, Gregory F.; Uesugi, Iichiro (Journal of Financial Stability, 2021)
Using unique micro data compiled from the real estate registry in Japan, we examine more than 400,000 loan-to-value (LTV) business loan ratios to draw implications for caps on LTV ratios as a macroprudential policy measure. We find that the LTV ratio exhibits counter-cyclicality, behavior that would have severely impeded the efficacy of a simple LTV cap had it been imposed. We also find that borrowers obtaining high-LTV loans are more risky but grew faster than those with lower LTV loans, which implies that a simple fixed cap on LTV ratios might inhibit growing (albeit risky) firms from borrowing.